2021
DOI: 10.1111/avj.13109
|View full text |Cite
|
Sign up to set email alerts
|

First direct human‐to‐cat transmission of the SARS‐CoV‐2 B.1.1.7 variant

Abstract: A highly transmissible severe acute respiratory coronavirus 2 (SARS‐CoV‐2) caused the coronavirus diseases 2019 (COVID‐19) pandemic, which resulted the highest morbidity and mortality rates among SARS‐CoV and MERS‐CoV. SARS‐CoV‐2 B.1.1.7 variant indicated the higher transmission among human‐to‐human and increasing hospitalisation. SARS‐CoV‐2 infection was observed in domestic animals showing human‐to‐pet transmission. In the current study, we report the first direct known human‐to‐cat transmission of the SARS‐… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
12
0
2

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(17 citation statements)
references
References 23 publications
(35 reference statements)
2
12
0
2
Order By: Relevance
“…Hematological parameters after challenge revealed a significant difference in the MCV between the PBS control and spike-alone injected groups on the one hand and the O/W- and alum-adjuvanted groups on the other. This is also consistent with the data from Curukoglu et al ( 36 ) where a slight increase in MCV was also detected after challenge. This suggests that the severity of SARS-CoV-2 infection impacts the MCV.…”
Section: Discussionsupporting
confidence: 93%
“…Hematological parameters after challenge revealed a significant difference in the MCV between the PBS control and spike-alone injected groups on the one hand and the O/W- and alum-adjuvanted groups on the other. This is also consistent with the data from Curukoglu et al ( 36 ) where a slight increase in MCV was also detected after challenge. This suggests that the severity of SARS-CoV-2 infection impacts the MCV.…”
Section: Discussionsupporting
confidence: 93%
“…However, during hematological examination of blood samples, we additionally found signi cant increase in the mean corpuscular volume (MCV) between the control animal (PBS) and Antigen alone vaccinated groups compared to the SWE-and Alum vaccinated groups of juvenile cats after challenge. This is also consistent with the data from Curukoglu et al [39] which have demonstrated the rst human to domestic cat transmission of SARS-CoV-2 with N501Y mutation (Alpha variant) in Northern Cyprus, where a slight increase in the MCV was detected, and cat did not show serious symptoms. In view of the above, this work demonstrates that the SWE-adjuvanted-and Alum-adjuvanted Spike vaccines against SARS-CoV-2 virus was able to induce high levels of virus-neutralizing antibodies in serum of vaccinated juvenile cats and that the induced response was able to prevent infection of the upper and lower respiratory tract, and the cardiovascular system.…”
Section: Discussionsupporting
confidence: 92%
“…Additionally, three case studies detected the alpha variant of SARS-CoV-2 in each case of natural infection, confirming the susceptibility of cats to this variant [ 22 , 26 , 42 ]. None of the included studies reported the detection of any other variant of concern.…”
Section: Resultsmentioning
confidence: 74%
“…Non-respiratory symptoms that were reported in different case studies included: Gastrointestinal symptoms [ 32 , 38 , 47 ], cardiac abnormalities [ 22 ], inappetence and apathy [ 28 , 38 ], ocular discharge [ 27 , 38 ], and fever [ 26 , 38 ]. …”
Section: Resultsmentioning
confidence: 99%